MOF precursor nitrogen-doped porous carbon / sulfur composite material as well as preparation method and application thereof

By using MOF precursors to prepare nitrogen-doped porous carbon/sulfur composites, the problems of dissolution of the positive electrode active material of sodium-sulfur battery and low sulfur conductivity are solved, and efficient electrochemical performance and long cycle life are achieved.

CN119480962AActive Publication Date: 2025-02-18ANHUI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411540491.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

In the large-scale use of sodium-sulfur batteries at room temperature, the positive electrode faces the problem of capacity loss and low sulfur conductivity due to dissolution of active substances.

Method used

Using MOF precursor nitrogen-doped porous carbon/sulfur composite material, MIL-88(B)-NH2 as the precursor, oxidize Fe3O4 nanoparticles after calcination, pickling and etching to obtain N-MPC, and sulfur enters microscope by melt diffusion method Pores to form N-MPC@S composite material.

Benefits of technology

Through the synergistic effect of multi-stage pore structure and nitrogen doping, the composite material improves the load efficiency of sulfur and the permeation of electrolyte, improves the ion transfer rate, and significantly improves the battery performance and cycle life of RT-Na/S batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480962A_ABST
    Figure CN119480962A_ABST
Patent Text Reader

Abstract

The invention provides an MOF precursor nitrogen-doped porous carbon / sulfur composite material and a preparation method and application thereof, and belongs to the field of material preparation.MIL-88 (B)-NH2 is used as a precursor for preparing porous carbon, after calcination, an iron element in MOF is oxidized into Fe3O4, nitrogen-doped carbon-coated Fe3O4 nanoparticles are obtained, finally, the Fe3O4 nanoparticles in a carbon shell are etched through acid pickling, and the nitrogen-doped porous carbon / sulfur composite material is obtained. The N-MPC is obtained; and sulfur powder enters micropores of the porous carbon through a melt diffusion method to obtain N-MPC (at) S which is used as the positive electrode of the RT-Na / S battery. And under the synergistic effect of the porous structure and nitrogen doping, excellent battery performance and excellent rate reversibility are shown in an RT-Na / S battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material preparation, and in particular relates to a MOF precursor nitrogen-doped porous carbon / sulfur composite material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are about to enter the commercial stage, and finding safer and more efficient energy storage materials remains a goal. The high abundance of sodium in the earth's crust makes the cost low, and the use of sulfur positive electrodes can achieve high energy density and large-scale deployment. However, for the large-scale use of room-temperature sodium-sulfur batteries, the following problems must be solved for the positive electrode: (1) Capacity loss caused by the dissolution of active substances after conversion to soluble intermediates; (2) The inherent low conductivity of sulfur itself.

[0003] The currently widely used strategy is to use polar carrier materials to bind polar polysulfides while providing a conductive framework; or to store sulfur in microporous carbon (MPC) with a porous structure to achieve physical confinement. Porous carbon materials have very broad prospects in the application of room temperature sodium-sulfur batteries. Many studies have reported porous carbon materials prepared by various methods, such as biomass carbon, metal organic framework (MOF) precursor-derived carbon composites, etc. For example, by adding polar nitrogen-containing groups to MOF. After treatment, uniformly distributed micropores can be formed to limit the shuttling of polysulfides.

[0004] Due to the differences in nuclear charge number and outermost electronic structure, doping nitrogen atoms in the carbon structure can introduce defects and increase the polarity of the material. It has been reported that polar nitrogen doping has a binding effect on polysulfides, which can improve the dissolution of polysulfides and inhibit the occurrence of the shuttle effect. Summary of the invention

[0005] The purpose of the present invention is to provide a MOF precursor nitrogen-doped porous carbon / sulfur composite material and a preparation method thereof, using MIL-88(B)-NH2 as a precursor for preparing porous carbon, oxidizing the iron element in the MOF to Fe3O4 after calcination, obtaining nitrogen-doped carbon-coated Fe3O4 nanoparticles, and finally etching the Fe3O4 nanoparticles in the carbon shell by acid washing to obtain N-MPC; sulfur powder enters the micropores of the porous carbon by melt diffusion to obtain N-MPC@S. The preparation method is simple and efficient.

[0006] Another object of the present invention is to provide an application of a MOF precursor nitrogen-doped porous carbon / sulfur composite material for sodium batteries.

[0007] The specific technical solutions of the present invention are as follows:

[0008] A method for preparing a MOF precursor nitrogen-doped porous carbon / sulfur composite material comprises the following steps:

[0009] 1) calcining MIL-88(B)-NH2, and then heating and acid washing the obtained N-Fe3O4@C to obtain N-MPC;

[0010] 2) Mixing N-MPC and sulfur, heating and reacting, and obtaining a N-MPC@S composite material.

[0011] In step 1), the calcination is performed at 600-800°C for 2h; the calcination protective atmosphere is high-purity argon; the heating rate is 5°C min -1 , raised to 600-800℃; during calcination, the air flow rate was 20mL min -1 .

[0012] In step 1), the preparation method of MIL-88(B)-NH2 is:

[0013] N, N-dimethylformamide and an iron source are mixed and evenly mixed, and then 2-aminoterephthalic acid and a sodium hydroxide solution are added. After stirring, the mixture is heated for reaction to obtain MIL-88(B)-NH2.

[0014] In the preparation method of MIL-88(B)-NH2, the amount ratio of the iron source and N,N-dimethylformamide is 0.028-0.032 mol / L, preferably 0.031 mol / L; the molar ratio of the iron source and 2-aminoterephthalic acid is 1:1; the concentration of the added sodium hydroxide solution is 2M, the volume ratio of N,N-dimethylformamide and sodium hydroxide solution is 35-40:1, and the iron source is selected from ferric chloride hexahydrate; the stirring, after stirring for 0.5h, the solution turns dark brown; the heating reaction, loading into a Teflon reactor, heating the reaction at 120°C in an oven for 8h; after the reaction is completed, after the reactor is completely cooled, the product is collected by centrifugation, washed alternately with deionized water and anhydrous ethanol three times each, and dried at 60°C overnight, and the product turns brown.

[0015] In step 1), the heated pickling uses N-Fe3O4@C and acid solution in a ratio of 1:30 g / mL; the acid solution used is concentrated hydrochloric acid with a mass concentration of 36%.

[0016] In step 1), the conditions for the heating pickling are: heating at 120° C. for 48 h;

[0017] In step 1), the heated pickling is carried out in a Teflon reactor. After the heated pickling is completed, the reactor is completely cooled and the product is collected by centrifugation. The product is washed with deionized water until the pH value of the clear liquid is 7, and finally washed once with anhydrous ethanol, and placed in a 60° C. oven for drying overnight to obtain N-MPC.

[0018] In step 2), the mass ratio of N-MPC to sulfur is 1:1;

[0019] In step 2), the heating reaction refers to: heating at 155°C for 15h under vacuum conditions, cooling, and then heating at 5°C / min -1 Heat to 200℃, nitrogen range, gas flow rate 20mL min -1 , after 0.5h, the sulfur on the surface of the material is removed to obtain the protective gas flow which is 99.999% pure argon.

[0020] The present invention first adopts 155℃ treatment for 15h because the solid orthorhombic sulfur powder will melt into liquid, at which time its viscosity is the lowest, which is most conducive to the molten sulfur penetrating into the matrix material under the action of capillary force. The treatment at 200℃ for 0.5h is to remove the unmelted sulfur on the surface of the material.

[0021] The present invention provides a MOF precursor nitrogen-doped porous carbon / sulfur composite material, which is prepared by the above method. The morphology of the MOF precursor nitrogen-doped porous carbon / sulfur composite material is a multi-porous hexagonal prism. The nanoscale hollow holes distributed in the material are cross-linked with each other in the material. The multi-level structure composed of macropores >50nm and micropores <2nm is conducive to improving the sulfur loading efficiency during the electrochemical reaction, and is also conducive to the penetration of the electrolyte and improving the ion transmission rate; the specific surface area of ​​N-MPC reaches 225m 2 g -1 .

[0022] The nanoscale hollow pores distributed in the material of the present invention are cross-linked with each other in the material. This multi-level structure composed of macropores (>50nm) and micropores (<2nm) is conducive to improving the sulfur loading efficiency during the electrochemical reaction. The macropores can provide sufficient space to buffer the volume expansion generated during the discharge process, and the small pores can effectively inhibit the occurrence of the polysulfide shuttle effect; at the same time, this structure is also conducive to the penetration of the electrolyte and improves the ion transfer rate. During the melt diffusion process, the S8 molecules diffuse into the microporous space of the material, so that the soluble polysulfides formed during the electrochemical reaction are confined to this space, achieving the effect of physical restriction. This nitrogen-doped multi-level pore cross-linked structure is an ideal carrier material for active sulfur in an ideal RT-Na / S battery.

[0023] The invention provides an application of a MOF precursor nitrogen-doped porous carbon / sulfur composite material for sodium batteries.

[0024] The present invention first prepares the precursor MIL-88(B)-NH2, oxidizes the iron element in the MOF to Fe3O4 after calcination, obtains Fe3O4 nanoparticles coated with nitrogen-doped carbon, and finally etches the Fe3O4 nanoparticles in the carbon shell by acid washing to obtain N-MPC. Sulfur powder enters the micropores of porous carbon by melt diffusion. Nitrogen-doped porous carbon is obtained by calcining and evaporating zinc elements at high temperature.

[0025] The chemical equation is:

[0026]

[0027] Compared with the prior art, the present invention uses MIL-88(B)-NH2 as a precursor for preparing porous carbon. After calcination, the iron element in MOF is oxidized to Fe3O4 to obtain nitrogen-doped carbon-coated Fe3O4 nanoparticles. Finally, the Fe3O4 nanoparticles in the carbon shell are etched by acid washing to obtain N-MPC; sulfur powder enters the micropores of porous carbon by melt diffusion. Nitrogen-doped porous carbon N-MPC@S is obtained by high-temperature calcination and evaporation of zinc elements, which is used as the positive electrode of RT-Na / S batteries. Under the synergistic effect of porous structure and nitrogen doping, excellent battery performance and excellent rate reversibility are shown in RT-Na / S batteries. At 0.1A g -1 At a current density of 1000 mA hg -1 ; At the same time at 2A g -1 Under high current density, the capacity is still 700mA hg after 3500 cycles. -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the preparation of the N-MPC@S composite material of the present invention;

[0029] Figure 2 The SEM photos of MIL-88(B)-NH2 prepared in Example 1 of the present invention with different N,N-dimethylformamide solvent dosages and different reaction times; (ab) is 40 mL of solvent for 8 h; (cd) is 40 mL of solvent for 10 h; (ef) is 40 mL of solvent for 12 h; (gh) is 30 mL of solvent for 8 h;

[0030] Figure 3SEM and TEM images of MIL-88(B)-NH2, N-Fe3O4@C and N-MPC prepared in Example 1; (ab) are SEM and TEM images of MIL-88(B)-NH2; (cd) are SEM and TEM images of N-Fe3O4@C; (ef) are SEM and TEM images of N-MPC;

[0031] Figure 4 The SEM and TEM images of MIL-88 (B), Fe3O4@C and MPC prepared in Comparative Example 1; (ab) are SEM and TEM images of MIL-88 (B); (cd) are SEM and TEM images of Fe3O4@C; (ef) are SEM and TEM images of MPC;

[0032] Figure 5 Element distribution diagrams of MIL-88(B)-NH2 prepared in Example 1 and MIL-88(B) prepared in Comparative Example 1; (ad) is the element distribution diagram of MIL-88(B)-NH2; (eh) is the element distribution diagram of MIL-88(B);

[0033] Figure 6 is the N-MPC EDS spectrum;

[0034] Figure 7 The XRD spectra, Raman spectra, thermogravimetric analysis spectra, nitrogen adsorption-desorption isotherms and pore size distribution diagrams of the products of Example 1 and Comparative Example 1; wherein (a) is the XRD spectra during the preparation process; (b) is the Raman spectrum; (c) is the thermogravimetric analysis spectrum; (d) is the nitrogen adsorption-desorption isotherms; and (e) is the pore size distribution diagram;

[0035] Figure 8 Energy spectrum analysis of N-MPC; (a) is the full XPS spectrum of N-MPC; (b) is the C1s high-resolution spectrum; (c) is the N1s high-resolution spectrum; (d) is the O1s high-resolution spectrum;

[0036] Fig. 9 The positive electrode of the RT-Na / S battery was prepared from the product N-MPC@S of Example 1 and the performance test and electrochemical characterization diagram of the half-cell were assembled; (a) is the N-MPC@S at a scan rate of 0.1 mV s -1 (b) CV curve of N-MPC@S at 100mA g -1 (c) The constant current charge-discharge curves of N-MPC@S at different current densities for the first three cycles; (d) The rate performance of N-MPC@S; (ef) The constant current charge-discharge curves of N-MPC@S at 100 mA g -1 , 1A g-1 Cyclic performance under current density; (g) is N-MPC@S at 2A g -1 Long cycle performance at current density;

[0037] Fig.10 The voltage curve and ex situ XRD spectrum of N-MPC@S in Example 1, wherein (a) is the voltage curve of N-MPC@S; (b) is the ex situ XRD spectrum;

[0038] Fig.11 The positive electrode of the RT-Na / S battery prepared by MPC@S in Comparative Example 1 and the performance test and electrochemical characterization diagram of the half-cell are assembled; (a) is the MPC@S at a scan rate of 0.1 mV s -1 (b) CV curve of MPC@S at 100mA g -1 The first three cycles of constant current charge-discharge curves under current density; (c) is the electrochemical impedance spectroscopy; (d) is the rate performance of MPC@S; (ef) is the MPC@S at 100mA g -1 , 500mA g -1 Cyclic performance of MPC@S at 1A g -1 Long cycle performance at current density;

[0039] Fig.12 Cyclic voltammetry curves of MPC@S and N-MPC@S at different scanning rates; (a, d) are the CV curves of MPC@S and N-MPC@S at different scanning rates; (b, e) are the log(ν)–log(i) plots corresponding to the peak positions of MPC@S and N-MPC@S; (c, f) are the contributions of pseudocapacitance of MPC@S and N-MPC@S at different scanning rates. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0042] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0043] The reagents used in the present invention are shown in Table 1. The instruments used are shown in Table 2.

[0044] Table 1 Reagents of the present invention

[0045] Reagents Specification Production Unit Ferric chloride Analytical grade Sinopharm Chemical Reagent Co., Ltd. Terephthalic acid Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. 2-Aminoterephthalic acid Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. N,N-Dimethylformamide Analytical grade Sinopharm Chemical Reagent Co., Ltd. Concentrated hydrochloric acid Sinopharm Chemical Reagent Co., Ltd. Anhydrous ethanol Analytical grade Sinopharm Chemical Reagent Co., Ltd. Sublimed sulfur Chemically pure Sinopharm Chemical Reagent Co., Ltd. Sodium Carboxymethyl Cellulose Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. SBR rubber 50% Nanjing Mojies Energy Technology Co., Ltd. Super conductive carbon black Electronic Grade CABOT Corporation Glass fiber diaphragm GF / D British Waterman Company Sodium trifluoromethanesulfonate Electronic Grade Shanghai Aladdin Biochemical Technology Co., Ltd. Diethylene glycol dimethyl ether Electronic Grade Shanghai Aladdin Biochemical Technology Co., Ltd. sodium ≥99% Sinopharm Chemical Reagent Co., Ltd. Copper Foil Electronic Grade Nanjing Mojies Energy Technology Co., Ltd.

[0046] Table 2 Instruments used in the present invention

[0047]

[0048]

[0049] Example 1

[0050] A method for preparing a MOF precursor nitrogen-doped porous carbon / sulfur composite material comprises the following steps:

[0051] 1) Preparation of MIL-88(B)-NH2:

[0052] Measure 30mL N,N-dimethylformamide, add 0.25g ferric chloride hexahydrate, stir to dissolve, add 0.17g 2-aminoterephthalic acid (PTA-NH2), add 0.8mL 2M NaOH solution, stir for 0.5h, the solution turns dark brown, put into Teflon reactor, and heat in oven at 120℃ for 8h. After the reactor is completely cooled, collect the product by centrifugation, wash with deionized water and anhydrous ethanol three times each, dry the product at 60℃ overnight, and the product turns brown.

[0053] The process was carried out according to step 1) of Example 1, except that the amount of N,N-dimethylformamide was 40 mL, the heating reaction time was 8, 10, and 12 h, and the morphology of the product was detected. The results are as follows: Figure 2 shown.

[0054] Figure 2 (af) show scanning electron microscope (SEM) photos of the product morphology obtained when the reaction temperature is 120°C and the amount of N,N-dimethylformamide used is 40 mL, and the reaction is performed for 8-12 hours respectively; Figure 2 The SEM photo (gh) in the figure is obtained when the reaction temperature is 120°C and the amount of N,N-dimethylformamide used is 30 mL and the reaction time is 8 hours. When the amount of solvent used is 40 mL, the concentration is reduced, resulting in a tendency to form particles with smaller particle sizes. As the reaction time increases, the particles will gradually break due to extrusion. When the amount of solvent used is reduced, the morphology of the particles obtained is more uniform at the same temperature, and no breakage occurs.

[0055] 2) Preparation of N-Fe3O4@C:

[0056] The dried MIL-88(B)-NH2 was crushed and loaded into a porcelain boat, which was then loaded into a tube furnace. After three pumping and three filling, high-purity argon was introduced for 0.5 h, and the heating rate was 5 °C min -1 , calcined at 650℃ for 2h, gas flow rate 20mL min -1 After the tube furnace has cooled down completely, the samples are taken out and they are all magnetic black powder, namely N-Fe3O4@C.

[0057] 3) Preparation of N-MPC:

[0058] The black powder N-Fe3O4@C prepared in step 2) was ground evenly, 1 g was weighed and loaded into a 40 mL Teflon reactor, 30 mL of concentrated hydrochloric acid was added, and the mixture was heated at 120° C. in an oven for 48 h. After the reactor was completely cooled, the product was collected by centrifugation, and the product was washed with deionized water until the pH value of the clear liquid was 7, and finally washed once with anhydrous ethanol, and dried in an oven at 60° C. overnight to obtain N-MPC.

[0059] 4) Preparation of N-MPC@S:

[0060] Weigh 0.1g of dried N-MPC and 0.1g of sublimed sulfur, grind them evenly, and put them into a quartz tube. Evacuate the tube and seal both ends. Put the quartz tube into an oven and heat it at 155℃ for 15h. After it is completely cooled, open the quartz tube and put it into a tube furnace. Heat it at 5℃min under a nitrogen protective gas flow. -1 Heat to 200℃, protective gas flow 20mL min -1 , and work for 0.5h to remove the sulfur on the surface of the material. Finally, a black solid with a slightly whiter and slightly pungent odor is obtained, which is N-MPC@S.

[0061] like Figure 1 The figure shows the preparation process of N-MPC. The precursor MIL-88(B)(-NH2) is prepared in a reactor using a simple solvent thermal method. After calcination, the iron element in the MOF is oxidized to Fe3O4 to obtain nitrogen-doped carbon-coated Fe3O4 nanoparticles. Finally, the Fe3O4 nanoparticles in the carbon shell are etched by acid washing to obtain N-MPC. Sulfur powder enters the micropores of porous carbon by melt diffusion. Nitrogen-doped porous carbon is obtained by evaporating zinc elements by high-temperature calcination.

[0062] The chemical equation is:

[0063]

[0064]

[0065] Comparative Example 1

[0066] A method for preparing a MOF precursor porous carbon / sulfur composite material comprises the following steps:

[0067] 1) Preparation of MIL-88 (B): The 2-aminoterephthalic acid in Example 1 was replaced with 0.156 g of terephthalic acid (PTA). After stirring, the solution showed orange-red color. Other conditions were the same as in Example 1. The dried product showed orange-red MIL-88 (B).

[0068] 2) Preparation of Fe3O4@C: According to Example 1, except that MIL-88(B)-NH2 was replaced by MIL-88(B), and the rest was the same as Example 1;

[0069] 3) Preparation of MPC: According to Example 1, except that N-Fe3O4@C is replaced by Fe3O4@C, the rest is the same as Example 1;

[0070] 4) Preparation of MPC@S: MPC@S was prepared according to Example 1 except that N-MPC was replaced by MPC.

[0071] Comparison of product detection and characterization in each step of Example 1 and Comparative Example 1:

[0072] Figure 3 (ab) are SEM and TEM photos of MIL-88(B)-NH2. From the photos, we can see that the size of MIL-88(B)-NH2 is about 0.9μm and MIL-88(B)-NH2 is a solid hexagonal prism. Figure 4 From the photo, we can see that MIL-88(B) is a solid octahedron.

[0073] Figure 3 (cd) are SEM and TEM photos of N-Fe3O4@C. The size is similar to that before calcination. The SEM photo shows that the surface is uneven, not as smooth as before calcination, and there are varying degrees of damage due to calcination. The TEM photo clearly shows the existence of light and dark fields in the material. The darker color is the Fe3O4 particles with poor conductivity, and the lighter color is the carbon layer with relatively good conductivity. The template particles of metal oxide are obtained by calcination.

[0074] Figure 3 (ef) are SEM and TEM images of N-MPC. Figure 4The SEM and TEM photos of MPC corresponding to (ef). It can be clearly observed from the SEM photo that after acid etching, the material is further damaged, while N-MPC can maintain its general morphology. MPC is almost damaged, and uneven holes can be observed on the surface, which corresponds to the TEM photo. The hollow structure distributed in the material can be observed from the TEM photo of N-MPC, and these nanoscale holes are cross-linked in the material. This multi-level structure composed of macropores (>50nm) and micropores (<2nm) is conducive to improving the sulfur loading efficiency during the electrochemical reaction. The macropores can provide sufficient space to buffer the volume expansion generated during the discharge process, and the small pores can effectively inhibit the occurrence of the polysulfide shuttle effect; at the same time, this structure is also conducive to the penetration of the electrolyte and improves the ion transfer rate. That is, during the melt diffusion process, the S8 molecules diffuse into the microporous space of the material, so that the soluble polysulfides formed during the electrochemical reaction are confined to this space, achieving the effect of physical restriction. This nitrogen-doped multi-level pore cross-linked structure is an ideal carrier material for active sulfur in RT-Na / S batteries. The present invention prepares nitrogen-doped and non-nitrogen-doped porous carbon materials. Although the morphology is partially damaged after high-temperature calcination and acid treatment, a multi-level porous structure can still be formed, proving that preparing a carbon-coated oxide template through MOF precursors and then etching oxide particles is a reliable method for preparing porous structures.

[0075] like Figure 5 The element distribution diagram shown in (ah) corresponds to MIL-88(B)-NH2 Figure 5 In (ad), the outlines of carbon and nitrogen can be clearly observed. The corresponding MIL-88 (B) Figure 5 In (eh), only the outline of carbon element can be observed, and the distribution of N element is not observed, which indicates that changing the group of ligand can introduce nitrogen doping into MOF. The EDS energy spectrum corresponding to N-MPC and MPC is shown in Figure 2. Figure 6 As shown, N-MPC has a characteristic energy spectrum peak of N element in the range of 0.35-0.42KeV, the atomic proportion reaches 6.32%, and the normalized mass reaches 5.78% (the mass proportion of N doped in N-MPC).

[0076] X-ray diffraction (XRD) of N-MPC preparation process Figure 7In (a), MIL-88(B)-NH2 and MIL-88(B) have almost the same spectra, proving that by changing the groups on the ligand, MOF crystals can grow in almost the same way, but there are differences in the growth orientation of different crystal faces. After calcination, they all formed cubic Fe3O4, space group Fd-3m(227), with obvious diffraction peaks (PDF#97-002-8664), and the three strong peaks of 30.124°, 35.483°, and 62.629° corresponded to (220), (311), and (440) crystal faces, respectively. At the same time, the characteristic diffraction peak of amorphous carbon appeared at about 20°. The N-MPC obtained by acid etching only had a broad peak of amorphous carbon at about 20° in XRD.

[0077] like Figure 7 (b) shows the Raman spectrum of N-MPC, 1300 cm -1 and 1500cm -1 The two strong peaks correspond to the D band (disordered vibration) and G band (sp 2 In-plane vibration of carbon), by calculating the I D / I G , due to the presence of nitrogen doping in N-MPC, I D / I G The value of is larger than that of MPC, which indicates that more defects are generated due to nitrogen doping. After N-MPC is compounded with sublimated sulfur, it can be clearly observed in the XRD spectrum (PDF#97-002-7261). The strongest peak at 23.124° corresponds to the (222) crystal plane. In the corresponding Raman spectrum, the peak at 469cm -1 、217cm -1 、150cm -1 Peaks corresponding to sulfur were observed.

[0078] As shown in the thermogravimetric (TGA) curve analysis of N-MPC@S in Figure 7 (c), a small amount of mass loss occurred at the beginning of heating, which may be due to the small amount of water and gas adsorbed in the material. After 150°C, due to the boiling point of sulfur, elemental sulfur evaporated and lost, and the loss rate reached a maximum at around 250°C. Most of the sulfur was completely lost before 300°C. After that, a small amount of mass loss was caused by the volatilization of sulfur that diffused into the micropores. In contrast, N-MPC showed a slow mass loss, which may be due to a small amount of adsorbed water and gas at the beginning. Continued heating may be caused by the loss of a small amount of chloride ions that were not completely removed. On the other hand, it is due to incomplete pyrolysis during the material preparation stage, further pyrolysis and graphitization. After calculation, the sulfur loading of N-MPC@S is about 44.5%.

[0079] Figure 7 The figure (d) shows the nitrogen adsorption-desorption isotherm of N-MPC@S. The specific surface area of ​​N-MPC without sulfur composite reached 225 m 2 g -1 During the test, the curve rises rapidly at relatively low pressure (P / P0≤0.015) and relatively high pressure (P / P0=0.4-1), which respectively represent the presence of macropores and micropores. In the intermediate pressure range, the curve also rises slowly, which represents the presence of mesopores in addition to macropores and micropores. After compounding with sulfur, the specific surface area of ​​N-MPC@S drops rapidly to only 9m 2 g -1 .from Figure 7 From the pore size distribution diagram corresponding to (e), it can be analyzed that the pore size before compounding is mainly distributed in the micropore and mesopore sizes; after compounding with sulfur, the micropore part completely disappears and the number of mesopores is significantly reduced, indicating that during the compounding process, sulfur enters the micropores and mesopores, achieving the storage effect.

[0080] The elemental composition and bonding type of N-MPC were investigated by X-ray photoelectron spectroscopy (XPS). Figure 8 The full spectrum of (a) can determine the presence of three elements: carbon, nitrogen, and oxygen, as well as a small amount of residual iron. Figure 8 In (b), the high-resolution spectrum of C1s corresponds to three peaks at 287.3 eV, 284.8 eV, and 283.9 eV, corresponding to C=O, CO, and CC bonds, respectively. Figure 8 The high-resolution spectrum of N1s corresponding to (c) can divide the nitrogen element into three types: oxidized nitrogen (404eV), pyrrolic nitrogen (399.8eV), and pyridinic nitrogen (397.5eV), which also matches the results of EDS energy spectrum and mapping characterization. Figure 8 The corresponding O1s high-resolution spectrum in (d) shows that the peaks at 532.5 eV, 531.3 eV, and 530.1 eV correspond to CO, C=O, and Fe3O4, respectively. Polar nitrogen doping is beneficial to the transfer of electrons and the adsorption of polysulfides by the carrier, which can effectively improve the capacity.

[0081] Example 2

[0082] An application of a MOF precursor nitrogen-doped porous carbon / sulfur composite material for sodium batteries, the specific method is as follows:

[0083] S1: Battery Assembly

[0084] After grinding 70mg N-MPC@S prepared in Example 1 with 20mg conductive carbon black for 0.5h, 200mg sodium carboxymethyl cellulose with a mass fraction of 6.54% and 0.1mL SBR rubber solution with a mass fraction of 5%, and 0.5mL deionized water were added to stir to form a homogenous slurry, and coated on copper foil, dried overnight in a vacuum drying oven at 60°C, and cut into circular electrode sheets with a diameter of 12mm. The active mass loaded by the electrode sheet was weighed on an electronic balance with an accuracy of one hundred thousandth, which was 0.9-1.1mg. In a glove box with a high-purity argon atmosphere (H2O<0.01ppm, O2<0.01ppm), the cut electrode sheets were assembled into button half-cells with a specification of CR2032. A glass fiber diaphragm with a specification of GF / D was used, and a diethylene glycol dimethyl ether solution with a concentration of 1M sodium trifluoromethylsulfonate was used as the electrolyte. The prepared electrode sheet was placed at the positive electrode, and metallic sodium was used as the negative electrode.

[0085] S2: Performance Test

[0086] On the Xinwei battery test system, the working window is set to 0.5-2.8V to complete the constant current charge and discharge, rate performance, constant current intermittent titration (GITT) test and the charge and discharge steps required for non-in-situ testing. Cyclic voltammetry curves, electrochemical impedance spectroscopy, ion migration rate, and pseudocapacitance tests are completed on the electrochemical workstation.

[0087] The N-MPC@S composite material was used as the positive electrode of the RT-Na / S battery and a half-cell was assembled for performance testing and electrochemical characterization. MPC@S was used as a comparison to analyze the effect of nitrogen doping on performance. Fig. 9 (a) shows N-MPC@S at 0.1mV s -1 At the scan rate, the first five CV curves within the electrochemical window of 0.5-2.8V are taken. There is an obvious reduction peak at around 0.75V in the first cycle. On the one hand, it is due to the side reaction caused by the formation of the SEI film. No peak appears at the same position afterwards, which proves this explanation. On the other hand, it is due to the peak shift caused by irreversible capacity loss, and then stabilizes at 0.9V. In the subsequent scanning process, four reduction peaks appear at 2.0V, 1.6V, 1.2V, and 0.9V respectively during the reduction process, and in the following Fig. 9 (b) at 100mAg -1The first three cycles of GCD curves under current density correspond. The reduction reaction corresponding to 2.0V is the conversion of S8 to Na2S8. This process is the key step in the shuttle effect of RT-Na / S battery. Solid Na2S8 is converted to liquid Na2S4, but this reaction process is not obvious in CV and completely disappears in the fourth and fifth cycles, which corresponds to the GCD curve. This shows that this conversion only occurs in the first two or three cycles. This is because it is only generated in the first cycle and all dissolved after participating in the first few cycles of reaction; the reduction peaks at 1.6V and 1.2V correspond to the conversion of Na2S4 to various short-chain polysulfides (Na2S x , 2≤x≤4), which is very stable in the CV scan, indicating that the reaction continues to occur stably in the subsequent cycle process; the reduction peak at 0.9V and the inflection point at this voltage in the corresponding GCD curve correspond to the conversion from Na2S2 to Na2S. In the subsequent oxidation process, the oxidation peak at 1.5V and the platform at the corresponding voltage in the GCD curve correspond to the conversion of various short-chain polysulfides to Na2S4, and the oxidation peak around 1.7V and the inflection point in the GCD curve correspond to the conversion of Na2S4 to Na2S8. The oxidation peak signal here is obviously weaker due to the faster kinetic process in the ether electrolyte. The oxidation peak that appears at around 2.2V corresponds to the reaction from Na2S8 to S8. There is no peak or platform of the S8 to Na2S8 reaction in the subsequent CV and GCD curves, and the intermediate process of N2S8 to Na2S4 is also very rapid, proving that the reaction is almost carried out in one step from S8 to Na2S4. The stability and overlap of the corresponding reaction peaks indicate that the electrochemical reaction process in this system is completely reversible. like Fig. 9 (c) shows the constant current charge and discharge curves at different current densities. It can be observed that the current density increases from 50 mA g -1 Increase to 2A g -1 During the charging and discharging process, the charge and discharge curves can maintain almost the same shape, which proves that the N-MPC@S composite material can also maintain excellent electrochemical performance under different current densities.

[0088] The performance of N-MPC@S composite battery was mainly tested, such as Fig. 9 (d) shows its rate performance, showing that the current density is from 0.05A g -1 , 0.1A g -1 , 0.2A g -1 , 0.5A g -1 , 1A g -1 , 2A g -1 , and then return to 0.05A g -1The discharge capacity step diagram during the process. During this process, as the current density increases, the discharge capacity decreases. This is because the faster kinetic process under high current may cause the electrochemical reaction to be incomplete, resulting in a lower capacity. The average capacity during this process reached 1452 mA hg -1 、1192mA hg -1 、1063mA hg -1 、962mA hg -1 、868mA hg -1 、744mA hg -1 、861mA hg -1 、955mA hg -1 、1040mA hg -1 、1102mA hg -1 、1142mA hg -1 The corresponding capacity retention rates are 78.6%, 92.4%, 97.8%, 99.3% and 99.2% respectively. At the same time, the discharge capacity of the first cycle reaches 1715mA hg -1 , which is very close to the theoretical capacity of sulfur, 1763 mA hg -1 , except for the first few cycles, due to the production of a small amount of soluble intermediates, the subsequent cycles showed excellent rate performance, which indicates that the prepared N-MPC@S composite material has excellent performance in adapting to continuously changing current density.

[0089] The N-MPC@S composites were subjected to constant current cycling tests at different current densities, such as Fig. 9 The values ​​shown in (eg) are 100mA g -1 , 1A g -1 , 2A g -1 Discharge capacity diagram during constant current cycling at three currents. Fig. 9 As shown in (e), at 100mA g -1 After 50 cycles at a current density of 1000 mA hg -1 , and there is a slow upward trend. This is due to the slow addition of sulfur deep inside the material to the electrochemical reaction process. Except for the first few cycles, the coulomb efficiency is always close to 100%, which shows that the increase in discharge capacity is not due to side reactions; 1Ag -1 At this current density, the capacity is still 850 mA hg after 350 cycles. -1During the cycle, the capacity remained relatively stable, and the coulomb efficiency was close to 100%. The capacity suddenly increased around 170 cycles and then returned to normal. This was because the ambient temperature rose, which increased the cycle capacity. When the ambient temperature returned to 25°C, the capacity returned to normal. This phenomenon also occurred at 2A g -1 In the long cycle of current density; at 2A g -1 In the long cycle under the current density, N-MPC@S showed an ultra-high cycle life of up to 3500 cycles, and it can still maintain 700mA hg after 3500 cycles. -1 The discharge capacity of the battery is about 100 cycles. The capacity increase in the first 100 cycles is caused by the gradual participation of deep sulfur in the electrochemical reaction. After this process, the capacity decreases slightly and tends to stabilize. Through the above constant current charge and discharge tests, the N-MPC@S composite material has shown a high cycle capacity, good rate performance, excellent cycle life and capacity retention rate in terms of battery performance.

[0090] In RT-Na / S batteries, the conversion of sulfur is carried out in multiple steps. In order to further study the electrochemical reaction process of N-MPC@S composite materials, non-in-situ XRD characterization was performed on them. The purpose is to measure the XRD of electrodes in different states and compare them to determine the phase changes during the electrochemical reaction. Select the position of the corresponding peak of CV, discharge / charge the battery to the specified voltage, disassemble the battery and perform XRD characterization, such as Fig.10 (a) shows the voltage position selected during the charge and discharge process. Fig.10 In (b), 41.5° and 50° correspond to Cu (PDF#97-005-3758). During the discharge process, the diffraction peaks of Na2S2 (PDF#89-2753) and Na2S (PDF#77-2149) gradually become more obvious and more numerous. In the subsequent charging process, their diffraction peaks gradually weaken and disappear. This also corresponds to the final discharge products Na2S2 and Na2S during the discharge process, which proves the complete process of sulfur in the charging and discharging process; and then the charging process gradually transforms into amorphous sulfur, so there is no obvious signal peak.

[0091] In order to prove that nitrogen doping improves the performance of RT-Na / S batteries, the MPC@S composite material prepared in Comparative Example 1 was also assembled into RT-Na / S batteries according to the method of Example 2 to study its electrochemical behavior and battery performance. Fig.11 (a) shows MPC@S at 0.1mV s -1Scan rate, the first five CV curves with 0.5-2.8V as the electrochemical window. Only in the first cycle of reduction process, a sharp reduction peak appeared at around 1.3V, which was due to the peak position shift caused by irreversible loss, and then stabilized at around 1.6V. In the subsequent scans, the position of the reduction peak was almost the same as that of N-MPC@S, showing similar electrochemical processes during the reduction process; but in the subsequent charge oxidation process, the oxidation peak at around 1.7V and the platform in the GCD curve corresponded to the conversion of Na2S4 to Na2S8, but the CV peak here often shifted during the scanning process, which may be caused by the irreversible loss of active substances. It is worth noting that MPC@S did not show the S8~Na2S8 conversion peak at 2.0V. As shown in the figure Fig.11 From the first three cycles of GCD curves in (b), it can be observed that MPC@S experienced more capacity loss during the first three cycles of charge and discharge, and this loss still occurred from the second to the third cycle, but this did not occur in N-MPC@S, indicating that nitrogen doping significantly improved the binding ability of polysulfides.

[0092] The impedance differences among N-MPC@S, MPC@S, N-MPC and MPC are compared. Fig.11 The electrochemical impedance spectroscopy (EIS) in (c) can be used to study their electrochemical kinetic performance. The semicircle part representing the high-frequency oscillation is related to the charge transfer in the electrode, and the straight line part corresponds to the low-frequency oscillation part of the sodium ion Warbug resistance. Through fitting, it can be seen that the charge transfer resistance of N-MPC is about 20Ω, slightly larger than the 10Ω of MPC. This is due to the presence of nitrogen doping, which leads to the generation of more defects, which will reduce the conductivity of the material; after N-MPC and MPC are compounded with sulfur, the corresponding charge transfer impedance increases. This is because the non-conductive sulfur reduces the conductivity of the carrier, reaching 35Ω and 20Ω respectively.

[0093] Some battery performance tests were also conducted on MPC@S, such as Fig.11 (d) shows that its rate performance shows that the current density is from 0.05A g -1 , 0.1A g -1 , 0.2A g -1 , 0.5A g -1 , 1A g -1 , 2A g -1 , and then return to 0.05A g -1 The discharge capacity step diagram during the process. During this process, as the current density increases, the discharge capacity decreases. This is because the faster kinetic process under high current may cause the electrochemical reaction to be incomplete, resulting in a lower capacity. The average capacity during this process reached 986 mA hg-1 、774mA hg -1 、693mA hg -1 、640mA hg -1 , 523mAh g -1 、450mA hg -1 、510mA hg -1 、585mA hg -1 、658mA hg -1 、717mA hg -1 、786mA hg -1 The corresponding capacity retention rates are 79.7%, 92.6%, 94.9%, 91.4% and 97.5%, respectively, showing good rate performance, but the discharge capacity is slightly lower than that of nitrogen-doped N-MPC, and there is a rapid capacity loss in the first few cycles, which may be due to the irreversible capacity loss caused by the shuttle effect between the load and the surface sulfur. Fig.11 100mAg shown in (e) -1 Cyclic test under current density, the first cycle discharge capacity reached 1360mA hg -1 After a large capacity loss in the first few cycles, the capacity stabilized at 950 mA hg after 100 cycles. -1 and tends to rise during the cycle, which is caused by the gradual participation of sulfur in the deep layer in the reaction; Fig.11 500mA g shown in (f) -1 Cyclic test under current density, the remaining capacity after 650 cycles is about 870mA hg -1 . Tests with higher currents were conducted, such as Fig.11 1A g shown in (g) -1 The long cycle test under current density showed that the capacity had a long rising process, which indicated that the electrolyte infiltration in MPC was not good, and the deep sulfur needed a long time to participate in the electrochemical reaction. After that, the capacity continued to decline. From the highest capacity point at the 150th cycle to the 1600th cycle, the remaining capacity was about 600mA hg -1 The capacity retention rate is only 83.4%, and the capacity loss rate per cycle reaches 0.058%. The above performance tests show that the lack of polar nitrogen in MPC and the lack of binding effect on polysulfides make the cycle stability and capacity retention rate of MPC unsatisfactory.

[0094] After that, the electrochemical kinetics of the material was studied, and the diffusion rate (D Na+ ). The formula used is:

[0095]

[0096] In this formula: τ is the set relaxation time, which is 600s in the present invention; mB is the mass of active material loaded on the electrode sheet; V M is the molar volume of the active substance; M B is the relative molar mass of the active substance; S is the area of ​​the electrode sheet, which is 1.131 cm in the present invention. 2 , ΔE S is the voltage change caused by the charge and discharge process, and ΔE t is the voltage change caused by the relaxation time. Usually, since the thickness of the active material after compaction is L<<100μm, if τ is related to L 2 / D GITT The calculated ion migration rate is considered reliable if there are multiple orders of magnitude differences between them. The GITT of the first cycle, the second cycle, and the fourth cycle of N-MPC@S were tested to compare the effect of nitrogen doping on the ion migration rate and the change of GITT during the cycle. GITT The average values ​​in different processes are shown in Table 3.

[0097] Table 3 Average values ​​of DGITT in different processes

[0098]

[0099]

[0100] From the calculated data, it can be seen that only during the first cycle of discharge, D GITT The value of D is small, which is due to the formation of SEI film during the first discharge process. In the subsequent cycles, whether charging or discharging, the measured D GITT The average value difference is not large and remains at a similar level. Compared with the N-MPC@S composite material, the D GITT This may be due to the fact that nitrogen doping produces more defects, which form more ion transmission channels, and the multi-level pore structure also makes ion transmission easier. In addition, through the distribution of scattered points, it is not difficult to find that at the position of the voltage platform corresponding to the constant current charge and discharge curve, D GITT The value of increases significantly and shows a more obvious peak shape, which may be caused by the large-scale migration of ions during the electrochemical process.

[0101] The N-MPC@S and MPC@S composites were subjected to 0.2 mV s -1 , 0.4mV s -1 , 0.6mV s -1 , 0.8mVs -1 , 1.0mV s -1 These cyclic voltammetry curves at different scan rates. Fig.12 By comparing the CV graphs at different scanning speeds shown in (a), it is not difficult to find that even at different scanning speeds, the shapes of the curves can still correspond well, which indicates that the polarization degree of the electrode is low. Generally speaking, in battery devices, electrodes have two behaviors to realize charge storage, namely Faraday behavior and capacitance. Faraday behavior is the energy transfer achieved by diffusion reaction in a general sense; the second describes the process of Faraday charge transfer through surface atoms or atoms close to the surface (pseudocapacitance) or non-Faraday double layer. Since the induced current (i) is related to the power of the scanning rate (ν), the following assumptions can be made, and the system can be analyzed through relevant calculations to determine the electrochemical behavior in the battery:

[0102] i=av b ;

[0103] log(i)=b log(v)+log(a);

[0104] Where a and b are constants, where the value of b can represent the capacity contribution due to capacitive behavior and intercalation behavior to a certain extent. If the b value is close to 1, it is controlled by capacitive behavior because the current of the capacitor is proportional to the scan rate (ν), and when the b value is close to 0.5, it means that the battery is controlled by the Faradaic diffusion behavior, where the current is proportional to the first power of ν.

[0105] like Fig.12 In (a), the locations where the electrochemical reactions occur are marked as peak 1 / 2 / 3 / 4 / 5. The values ​​of the corresponding peak positions at different scan rates are fitted, such as Fig.12 The log(ν)–log(i) graph of the peak current is given in (b). The b values ​​obtained by linear fitting the slopes of the peak values ​​of the five peaks are 0.644590, 0.69736, 0.74125, 0.4778, and 0.70913, respectively, which indicates that diffusion behavior dominates the electrochemical reaction process. By performing error analysis on the fitted data, the variances obtained are 0.98628, 0.99779, 0.99940, 0.99065, and 0.99417, respectively. The variance values ​​are close to 1, indicating that the fitted data are highly reliable.

[0106] By dividing the response current (i) at a certain voltage (V) into two parts, namely, capacitance contribution and diffusion, the contribution of pseudocapacitive behavior at different scan rates is further analyzed. e Dun n Research: i(V)=k1v+k2v 1 / 2 ;

[0107] Through calculation, we know that Fig.12 As shown in (c), at the corresponding scanning speeds, the corresponding pseudocapacitance contributions are 17.9%, 29.1%, 38.8%, 47.6% and 53.5%, respectively, which indicates that the charge stored in the battery of this system mainly comes from the contribution from diffusion behavior.

[0108] like Fig.12 As shown in (df), the MPC@S composites were subjected to the same tests as above. Fig.12 The peaks 1 / 2 / 3 / 4 / 5 marked in (d) are as follows: Fig.12 The log(ν)–log(i) graph of the peak current is given in (e). The b values ​​obtained by calculating the slopes of the five peak fitting lines are 0.40977, 0.78637, 0.33072, 0.72181, and 0.69530, respectively. Compared with the N-MPC@S composite material, the contribution of pseudocapacitive behavior at the corresponding peak position has increased; by performing error analysis on the fitted data, the variances obtained are 0.99401, 0.99670, 0.98935, 0.99263, and 0.99913, respectively, and the variance values ​​are very close to 1, which proves that the fitted data are highly reliable; Fig.12 The pseudocapacitive contributions at different scanning speeds in (f) are 75.1%, 81.2%, 86.9%, 89.2%, and 94.0%, respectively, indicating that pseudocapacitive behavior dominates in this system.

[0109] From the above performance comparison of N-MPC@S and MPC@S, it can be seen that the change in behavior may be due to the large number of defects caused by nitrogen doping in the prepared N-MPC@S composite material. At the same time, there are a large number of porous structures, which construct a large number of channels for ion transport, so that in the process of electrochemical reaction, the kinetic process reaction in the electrochemical hardening process is accelerated, and the electrochemical reaction has more capacity contribution at a large rate and has better rate performance.

[0110] In the present invention, nitrogen-doped MOF precursors and porous carbon are obtained by using amino-containing ligands; the composite material prepared by combining the prepared nitrogen-doped porous carbon with sulfur is applied to the positive electrode of the RT-Na / S battery, and compared with the composite material without nitrogen, it is proved that it has a certain effect on binding polysulfides; N doping is introduced into MOF by changing the ligand and contrasting it, and the use of EDS, XPS and other characterizations proves that this method can introduce nitrogen doping into porous carbon; and the results of non-in situ characterization of the electrochemical charge and discharge process show that porous carbon has a physical restriction effect on polysulfides. That is, the synergistic effect generated by the physical structure and polarity is used to inhibit the occurrence of polysulfide "shuttling", which effectively improves the cycle life and capacity retention rate of the battery. Under the synergistic effect of the porous structure and nitrogen doping, excellent battery performance and outstanding rate reversibility are shown in the RT-Na / S battery, at 0.1A g -1 At a current density of 1000 mA hg -1 ; At the same time at 2A g -1 Under high current density, the capacity is still 700mA hg after 3500 cycles. -1 .

[0111] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a MOF precursor nitrogen-doped porous carbon / sulfur composite material, characterized in that: The preparation method comprises the following steps: 1) calcining MIL-88(B)-NH2, and then heating and acid washing the obtained N-Fe3O4@C to obtain N-MPC; 2) Mixing N-MPC and sulfur, heating and reacting, and obtaining a N-MPC@S composite material.

2. The preparation method according to claim 1, characterized in that: In step 1), the calcination refers to calcination at 650° C. for 2 h.

3. The preparation method according to claim 1, characterized in that: In step 1), the preparation method of MIL-88(B)-NH2 is: N,N-dimethylformamide and an iron source are mixed, and after mixing, 2-aminoterephthalic acid is added, stirred, and heated to react to obtain MIL-88(B)-NH2; the usage ratio of the iron source to N,N-dimethylformamide is 0.028-0.032 mol / L.

4. The preparation method according to claim 1, characterized in that: In step 1), the heated pickling, the amount ratio of N-Fe3O4@C and acid solution used is 1:30g / mL; the acid solution used is concentrated hydrochloric acid.

5. The preparation method according to claim 1 or 4, characterized in that: In step 1), the conditions for the heating pickling are: heating at 120° C. for 48 hours.

6. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of N-MPC to sulfur is 1:

1.

7. The preparation method according to claim 1, characterized in that: In step 2), the heating reaction refers to: heating at 155°C for 15h under vacuum conditions, cooling, and then heating to 200°C by 5°C, with a protective gas flow of 20mL min -1 , 0.5h is needed to remove the sulfur on the surface of the material.

8. A MOF precursor nitrogen-doped porous carbon / sulfur composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The MOF precursor nitrogen-doped porous carbon / sulfur composite material has a porous hexagonal prism shape.

9. An application of the MOF precursor nitrogen-doped porous carbon / sulfur composite material according to claim 8, characterized in that: For use in sodium batteries.

Citation Information

Patent Citations

  • Fuel cell negative electrode catalyst and preparation method and application thereof

    CN109449448A

  • MOF-sulfur materials and composite materials, methods of making same, and uses thereof

    US20220158173A1